DAMPAK PERSON-ORGANIZATION FIT TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASI - Renita Yeldiana Kodarisman; Meily Margaretha (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aimed to examine the effect of person-organization fit, job satisfaction and organizational commitment in PT Telkom Bandung. The method used by the researcher is a quantitative method using a simple linear regression technique. The data used in this study are secondary and primary data, through the distribution of questionnaires using a Likert scale and data collection of 24 questions which were distributed to 100 employees of the information technology section of the Bandung telecommunications company. The results of the research proved that the two hypotheses proposed in this study are accepted, po-fit has positive influence to job satisfaction and organizational commitment. Based on the result of the study, the company is expected in the employee recruitment process, must pay attention to the compatibility between prospective employees and the company, not only compatibility with their jobs. Then when assigning employees, the company does not only consider the ability of employees, but also pay attention to the compatibility between employees and the departments they will handle, and the company should continue mainting employee commitment in order to improve the performance of employees.